2017
DOI: 10.1016/j.afjem.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

African emergency care providers’ attitudes and practices towards research

Abstract: IntroductionEmergency care research in Africa is not on par with other world regions. The study aimed to assess the perceptions and practices towards research among current emergency care providers in Africa.MethodsA survey was sent to all individual members of the African Federation of Emergency Medicine. The survey was available in English and French.ResultsOne hundred and sixty-eight responses were analysed (invited n = 540, responded n = 188, 34.8%, excluded n = 20). Responders’ mean age was 36.3 years (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…This survey evaluated the attitudes and practices towards research in emergency medicine, of which 77.4% were practicing in Africa. 11 The most prominent barrier listed was lack of research funding (64.3%). Other barriers included a lack of training opportunities, research time, and research culture.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…This survey evaluated the attitudes and practices towards research in emergency medicine, of which 77.4% were practicing in Africa. 11 The most prominent barrier listed was lack of research funding (64.3%). Other barriers included a lack of training opportunities, research time, and research culture.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…Our survey showed that the main driving force to publish was to add to the body of knowledge. This opinion differed from a recent study that suggested that 70% of African emergency care providers get involved in research in order “to get published” [9] , above “improving clinical care and patient-centred outcomes” [9] . The most common reason for failing to publish was lack of time.…”
Section: Discussionmentioning
confidence: 67%
“…Although publication in a high impact journal is often seen as the pinnacle of dissemination, it does not necessarily reach the most appropriate audience [17] . Around half of African researchers frequently experience poor access to research due to access charges [9] . Disseminating information to the community involved should be prioritised especially as research in most African settings is only just developing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Hoving et al reported that 58% of African emergency care researchers struggled frequently with publication access, suggesting that local emergency care researchers are unable to make do given poor access and the significantly higher out-of-pocket expense related to publication. 14 The combination of these elements creates a perfect storm that threatens the growth and development of the specialty locally. Fortunately, article-processing fee waivers and discounts exist for low-middle and low income countries, which is likely why African authors were able to publish via open access more regularly.…”
Section: Discussionmentioning
confidence: 99%